RESPON SISWA DAN GURU TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA ARAB DI SMPIT DARUL FIKRI SIDOARJO - Alfaruqi Abdulloh, Ibrahim; Hikmah, Khizanatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses student and teacher responses to the implementation of the Independent Curriculum (Kurikulum Merdeka) in Arabic language learning at SMPIT Darul Fikri Sidoarjo. This research employs a qualitative method with a descriptive approach, aiming to describe perceptions, experiences, and challenges encountered in its application. Data was collected through interviews and questionnaires involving 51 eighth-grade students and one Arabic language teacher. The findings indicate that students benefit from more flexible and practice-based learning methods, which enhance their understanding and interest in Arabic. Teachers also experience greater flexibility in designing teaching strategies, although they still face challenges in material preparation and limited supporting facilities. Overall, the implementation of the Independent Curriculum in Arabic language learning at SMPIT Darul Fikri Sidoarjo has had a positive impact, yet further optimization in technical aspects and learning facilities is needed for greater effectiveness.